Response to gluten free diet in sero-positive celiac disease children suffering from severe acute malnutrition in age group 1-5 years - Meena, Mahendra; Meena, Pradeep; Suman, R. L.; Goyal, Suresh (International Journal of Contemporary Pediatrics, 2019)
Background: Diagnosis of celiac disease in children suffering from severe acute malnutrition without duodenal biopsy or HLA typing is a dilemma. The objective of this study was to study the response to gluten free diet in sero-positive Celiac Disease children suffering from severe acute malnutrition in age group 1-5 years. Methods: This prospective, observational, hospital-based study was conducted at MTC of tertiary care medical college hospital of southern Rajasthan from Dec. 2017 to Nov. 2018. Total 110 children with SAM were enrolled and screened for celiac disease on the basis of tissue tTg-IgA/IgG serology. Seropositive cases were kept on gluten free diet for short period of time and observed for the resolution of symptoms and improvement in growth, monitored by anthropometry on discharge and follow up visit. Results: Mean weight gain (gm/kg/day) on follow up was 3.87±3.49 in seropositive and 1.88±3.79 in seronegative cases (P-value<0.05). Mean weight gain was 6.43±3.28gm/kg/day in only tTg-IgA positive and 3.04±2.95 gm/kg/day in only tTg-IgG positive cases (P-value-<0.05). The mean weight gain in strictly gluten free adherent sero-positive cases was 4.89±2.97 gm/kg/day while in gluten free non-adherent patients it was -0.49±1.70 (P-value <0.001). Mean weight gain in probable (tTg-Ig-A <10 times ULN) and presumptive (tTg-IgA >10 times ULN) Celiac disease were 3.44±3.73 and 5.44±3.78, respectively without statically significant difference (P-value >0.05). Conclusions: In situations where facility of duodenal biopsy and or HLA DQ2/DQ8 typing is not available, resolution of symptoms and improvement in growth on gluten free diet confirms the diagnosis of celiac disease.